DESAIN PENGUKURAN KINERJA PERUSAHAAN MEDIA TELEVISI DAERAH PADA BANYUWANGI TV DALAM KERANGKA BALANCED SCORECARD - Ibanatuz Zuhro Siamu Mubarokah; Siti Maria Wardayati; Agung Budi Sulistiyo (ITB AAS INDONESIA, 2022)
Banyuwangi TV performance measurement using traditional performance measurement only focuses on the financial. It has made an employee performance assessment which is commonly referred to as an Assessment manual. Manual assessment is a system of measuring or evaluating employee performance which is carried out manually by the company. This assessment is carried out every 6 months and has been running since 2019-2020. The purpose of this study was to analyze the performance measurement design of regional television media companies on Banyuwangi TV within the framework of the balanced scorecard. The author uses a qualitative method with a case study approach. The stages of performance measurement design include making company strategic goals based on the Balanced Scorecard, Company Strategy Map, process identification, making Key Performance Indicators (KPI) and weighting. In the perspective of the balanced scorecard, there are 4 perspectives, namely the financial perspective which produces 3 strategic objectives, the customer perspective produces 5 strategic objectives, the internal business process perspective produces 6 perspectives and the learning and growth perspective produces 4 strategic objectives. The formulation of key indicators that are compiled in key performance indicators (KPI) there are 25 KPIs consisting of 6 KPIs from a financial perspective, 7 KPIs from a customer perspective, 8 KPIs from an internal business perspective and 4 KPIs from a learning and growth perspective.